2002
DOI: 10.1107/s0907444902014476
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme crystal growth kinetics in microgravity

Abstract: Mach-Zehnder interferometry is applied to quantitatively characterize growth of lysozyme crystals in microgravity. Experiments were performed by the Free Interface Diffusion technique into APCF FID reactors using large seeds. Tracking of the experiments using interferometry allowed to monitor the onset of supersaturation and the seed growth. A large and stable concentration depletion zone around the growing crystal developed, whose time evolution was analyzed. The interferograms were analyzed taking into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
0
21
1
Order By: Relevance
“…These improvements in the crystal quality are attributed to the gel-growth method for the following reasons: (1) within the hydrogel, mass transport is essentially controlled by diffusion; and (2) the protein concentration gradient (depletion zone) generated by each crystal during its growth is not destroyed by density-driven convective flow or by sedimentation [24][25][26]. These improvements in the crystal quality are attributed to the gel-growth method for the following reasons: (1) within the hydrogel, mass transport is essentially controlled by diffusion; and (2) the protein concentration gradient (depletion zone) generated by each crystal during its growth is not destroyed by density-driven convective flow or by sedimentation [24][25][26].…”
mentioning
confidence: 99%
“…These improvements in the crystal quality are attributed to the gel-growth method for the following reasons: (1) within the hydrogel, mass transport is essentially controlled by diffusion; and (2) the protein concentration gradient (depletion zone) generated by each crystal during its growth is not destroyed by density-driven convective flow or by sedimentation [24][25][26]. These improvements in the crystal quality are attributed to the gel-growth method for the following reasons: (1) within the hydrogel, mass transport is essentially controlled by diffusion; and (2) the protein concentration gradient (depletion zone) generated by each crystal during its growth is not destroyed by density-driven convective flow or by sedimentation [24][25][26].…”
mentioning
confidence: 99%
“…The formation of a stable depletion zone in diffusive setups minimizes and stabilizes the supersaturation at the crystal/solution interface, reducing and making constant the growth rate, which kinetically favors the arrangement of molecules at the crystal surface and allows for efficient transport of impurities out of it. This is generally accepted as a factor enabling crystal perfection [17][18][19][20]. Therefore, it was concluded that the diffusive mass-transport conditions created during microgravity experiments are a key factor in obtaining good quality protein crystals [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure usually employed in these studies consists in growing a very limited number ͑N͒ of "seeds" ͑see, for instance, the excellent works of Otálora et al ͓4,5͔,Lee and Chernov ͓6͔,etc.͒. In practice, multiple-nucleation events are obtained in gel ͓N = O͑100͔͒ usually by a counter diffusion technique ͑for further details about this technique and its models see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%